2005
DOI: 10.1128/aem.71.7.3624-3632.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacteria Growing in Natural Mineral Water after Bottling

Abstract: Bacterial growth occurs in noncarbonated natural mineral waters a few days after filling and storage at room temperature, a phenomenon known for more than 40 years. Using the full-cycle rRNA approach, we monitored the development of the planktonic bacterial community in a noncarbonated natural mineral water after bottling. Seven 16S rRNA gene libraries, comprising 108 clones in total, were constructed from water samples taken at various days after bottling and from two different bottle sizes. Sequence analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
64
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 53 publications
13
64
0
2
Order By: Relevance
“…Loy and coworkers recently reported that less than 3% of the total population gave a positive signal with a bacterial probe (Fig. 4) (at 0 days) in bottled mineral water (22). Similarly, Kalmbach and coworkers observed a positive probe signal from a small fraction (Ͻ23%) of planktonic bacteria in a German water distribution system (15).…”
Section: Proteobacteriamentioning
confidence: 90%
“…Loy and coworkers recently reported that less than 3% of the total population gave a positive signal with a bacterial probe (Fig. 4) (at 0 days) in bottled mineral water (22). Similarly, Kalmbach and coworkers observed a positive probe signal from a small fraction (Ͻ23%) of planktonic bacteria in a German water distribution system (15).…”
Section: Proteobacteriamentioning
confidence: 90%
“…It has been found to make up 2-53% of the cells found in drinking water system biofilms in Germany (Kalmbach et al, 2000), and Loy et al (2005) noted that they commonly make up a large portion of the microbial communities found in bottled natural mineral water. It made up 2.7% of the sequences from Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, phylogenetic analysis of selected DGGE bands identified bacteria associated with groups typically found in freshwater biofilms (Alpha-, Beta-, and Gammaproteobacteria and Bacteroidetes). Four of eight sequences belonged to the Betaproteobacteria, which have been found to be the most abundant bacterial group in freshwater ecosystems (11,16,24). Araya and colleagues (4) proposed that Betaproteobacteria may attach more easily to surfaces during initial biofilm formation than other groups of bacteria and, thus, dominate biofilm succession.…”
Section: Microbial Community Successionmentioning
confidence: 99%